การพัฒนาแนวทางการดำเนินงานตามระบบดูแลช่วยเหลือนักเรียนในโรงเรียนขนาดเล็กสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี เขต 1 - แก้วแก่น, รัชนู (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
The aims of this research were to1) investigate the state and the desirable conditions of implementation of the system care and assistance student in small- sized schools under the office of Udonthani primary educational service area 1 and 2) development of guideline implementation of the system care and assistance student in small- sized schools. The study consisted of two phases : the first phase, investigating the state and the desirable conditions of implementation of the system care and assistance student in small- sized schools under the office of Udonthani primary educational service area 1 The 92 school administrators and the 214 teachers the second phase, 3 school administrators and the 9 teachers the developed the guideline was assessed by 5 experts. The tools used to collect data were the five-star rating scale questionnaire of 50 questions on the state and the desirable conditions of teacher for implementation of the system care and assistance student, the discrimination .43 -.78 and the reliability 0.98, and Query adverse conditions of teacher for implementation of the system care and assistance student, the discrimination .50 - .77 and the reliability 0.98, the structured interview and guideline assessment. The statistics used for data analysis were mean, standard deviation, and percentage. The findings indicated that 1) the state conditions of implementation of the system care and assistance student in small- sized schools under the office of Udonthani primary educational service area 1 was at a moderate level. The standard with highest mean was the second components for student screening. For the desirable conditions of the state and the desirable conditions of implementation of the system care and assistance student in small- sized schools , it was found that overall mean was at a high level. The standard with highest mean was the third components for promotion 2) The guideline of development of guideline implementation of the system care and assistance student in small- sized schools under the office of Udonthani primary educational service area 1 consisted of five components; that is, the knowing of individual student 5 choices, student screening 5 choices, student supporting and developing 5 choices, student preventing and resolving 5 choices and student transfer 5 choices. The outcomes of assessing guideline of development of guideline implementation of the system care and assistance student in small- sized schools showed that appropriateness was at a high level and the possibility was at a high level.